Digital Breast Tomosynthesis: Clinical Operations. Issue 2 (11th May 2019) - Friedewald, Sarah M; Bhole, Sonya; Wang, Lilian; Gupta, Dipti
Abstract: Digital breast tomosynthesis (DBT) is rapidly becoming the standard of care for breast cancer screening. Implementing DBT into practice is relatively straightforward. However, there are important elements of the transition that one must consider to facilitate this process. Understanding the Digital Imaging and Communications in Medicine (DICOM) standard for DBT, as well as how images are displayed, is critical to a successful transition. Standardization of these processes will allow easier transmission of images from facility to facility, and limit the potential for errors in interpretation. Additionally, recent changes in federal regulations will require compliance with mandated training for the radiologist, technologist, and physicist, as well as accreditation for each DBT unit. These regulations aim to ensure high-quality imaging across the country as has been previously seen with standard digital mammography. Synthesized imaging is the most recent improvement for DBT, potentially obviating the need for a simultaneous traditional digital mammogram exposure. Studies have demonstrated near equivalent performance when comparing the combination imaging of DBT and digital mammography versus DBT combined with synthetic imaging. As the quality of the synthetic images continues to improve, it is increasingly likely that it will replace the traditional mammogram. Adherence to DBT-specific parameters will enhance the physician experience and ultimately translate to increased cancer detection and fewer false positive examinations, benefiting all women who are screened for breast cancer.